Expert knowledge elicitation on African Swine Fever and outdoor farming of pigs. Issue 6 (9th June 2021) - Hart, Andy; Rowe, Gene; Bolger, Fergus; Colson, Abigail
Abstract : An expert knowledge elicitation was conducted to address three tasks identified by EFSA's Animal Health and Welfare (AHAW) Panel: categorize outdoor farm types of pigs in EU MS according to the risk of African Swine Fever (ASF) introduction into these farms and the risk of ASF spread from these farms, rank biosecurity measures according to their potential to lower the risk of ASF introduction into these farms and the risk of ASF spread from these farms in ASF‐affected countries, and propose improvements of biosecurity for outdoor pig farming categories and the control measures that should flank these in ASF‐affected countries. The elicitation was conducted with four scientists with expertise in ASF epidemiology, biosecurity and outdoor farming practices and structures, including organic and backyard farming of pigs outdoors. The first task was addressed by eliciting estimates for the risk of new ASF outbreaks in the areas of interest in the coming year for two types of outdoor pig farms, specified by EFSA. As a worst‐case scenario for assessment, the EKE considered areas of the EU where ASF is present in wild boar and in domestic pigs in indoor farms and, if outdoor farms were to be permitted in such areas, in domestic pigs in outdoor farms. The second task was addressed by developing a preliminary list of biosecurity measures, prioritising 7 measures in terms of expected effectiveness in reducing risk for each farm type, and then eliciting estimates of the effectiveness, feasibility and sustainability of each of the prioritised measures, considered separately. The third task was addressed by brainstorming of potential control measures to be considered in conjunction with improved biosecurity. The results are intended for consideration by the EFSA AHAW Panel when developing a Scientific Opinion on ASF and outdoor pig farming. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.6639/full